A prolactin-targeting antibody to prevent stress-induced peripheral nociceptor sensitization and female postoperative pain - Harrison J. Stratton; Mahdi Dolatyari; Carol Kopruszinski; Andre Ghetti; Stephanie Maciuba; Greg Bowden; Pierre Rivière; Kara Barber; David W. Dodick; Edel Edorh; Nicolas Dumaire; Aubin Moutal; et al. (Proceedings of the National Academy of Sciences, 2025)
Scheduled surgeries elicit stress in many patients. Levels of preoperative stress, anxiety, and female gender are known risk factors for increased and prolonged postoperative pain. The mechanisms by which psychological stress increases postoperative pain, especially in women, remain unknown. We hypothesized that stress amplifies postoperative pain by sensitizing dorsal root ganglion (DRG) nociceptors. Prolactin (PRL) is a female-predominant neurohormone that is controlled by estrogen and stress. PRL signals at the prolactin receptor long (PRLR-L) and short (PRLR-S) isoforms to induce gene transcription and nociception, respectively. Critically, prolactin sensitizes female, but not male, murine, Macaque and human nociceptors, revealing an evolutionarily conserved mechanism with high translational potential for human therapy. Prior restraint stress (RS) increased the magnitude and duration of incisional injury–induced postoperative pain hypersensitivity in both male and female mice. In females, RS or incisional injury downregulated PRLR-L and increased PRL-dependent nociceptor excitability. Female selective inhibition of postoperative pain hypersensitivity was produced by a) pharmacological inhibition of pituitary PRL b) overexpression of DRG PRLR-L to bias PRL signaling away from PRLR-S and c) CRISPR/Cas9 editing of PRLR isoforms. PL200,019, our recently discovered monoclonal antibody against human PRL (hPRL), prevented hPRL-induced sensitization of human female nociceptors. Using female mice genetically modified to express hPRL, rather than murine PRL, PL200,019 prevented both stress and incisional injury–induced hypersensitivity. Preemptive inhibition of stress-induced nociceptor sensitization with a monoclonal antibody to sequester PRL can improve female postoperative pain, diminish the need for postoperative opioids and decrease the risks of transition to chronic pain.